Raising standards in literacy - Fisher, Ros; Brooks, Greg, 1944-; Lewis, Maureen (Language and literacy in action series., 2002)
This book represents the best current thinking and research about literacy, being the outcome of a series of high-profile seminars on raising standards in literacy. Research, progress in this area and its development is focused on.